Facile sorbent from esterified cellulosic sago waste for engine oil removal in marine environment - Zainab, binti Ngaini; Farid, bin Noh; Rafeah, binti Wahi (Center for Environmental and Energy Research and Studies, 2018)
This article reports on the utilization of chemically modified cellulosic sago (MCS) from sago bark as a highly potential material for remediating oil spills in marine environment. MCS was prepared via incorporation of hydroxyl-rich cellulosic sago bark (CS) with fatty acid derivative. The sorption capacity, hydrophobicity, and lipophilicity of MCS and CS were evaluated. MCS exhibited higher total pore volume (0.012 cm3/g) and high hydrophobicity (60%) compared to CS. The oil spills adsorption studies was compared in batch system both in deionized water and seawater. MCS showed higher oil sorption capacity in deionized water after 60 min (MCS 3.0 g/g, CS 2.4 g/g). The maximum oil sorption capacity of MCS in dynamic seawater system was 5.7 g/g which was higher than CS (5.0 g/g). The results suggested that MCS is a potential low-cost natural sorbent which work best in the removal of oil spilled from dynamic seawater environment than deionized water. © 2017, Islamic Azad University (IAU).